Attitude and Ideology in Media Reporting: A Case Study of Kompas's Coverage of the Free Nutrition Meals Program - Sakut Anshori; Jumatul Hidayah; Abd. Rahman Zain (Linguists : Journal of Linguistics and Language Teaching, 2024)
This study analyzes the language used by Kompas, focusing on the expression of attitude. The appraisal framework developed by Martin and White (2005) is used as an analytical linguistics tool to investigate aspects of attitude—affect, judgment, and appreciation—to identify the ideological position through a critical discourse analysis (CDA) of four online texts about the Free Nutrition Meals Program (FNMP). This qualitative research employs a content analysis method to interpret attitude resources utilized in constructing news texts. The results of the study reveal that Kompas demonstrates a relatively balanced representation of both positive and negative attitudes (53.8% positive, 46.2% negative). This equilibrium between positive and negative attitude data indicates significant and contentious issues faced by the government, political observers, and the general public regarding the FNMP. These findings illustrate how news reporting by media outlets can reflect ideological orientations and influence public perceptions regarding FNMP. Additionally, this study provides practical insights that can be utilized by media content creators and journalists to craft messages that are more effective and tailored to the intended audience. When presenting news that includes positive and negative assessments, it is crucial to maintain "impartial" and "balance" in news delivery, in accordance with journalistic ethics. In the context of EFL, this study also has significant implications for enhancing students' discourse competence.